2008
DOI: 10.1108/19852510880000634
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Ownership Structure and Earnings Management

Abstract: This study examines the relation between managerial ownership structure and earnings management. Unlike previous research which treats insiders as a homogeneous group, we further classify insiders into executives, outside directors, and blockholders to conduct an in-depth study. Earnings management is captured by discretionary accruals that are estimated using the modified Jones model. For a large sample of Taiwanese listed firms over the period 1997 and 2004, we find that discretionary accruals first increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 37 publications
6
49
2
1
Order By: Relevance
“…The adjusted Jones Model (Dechow et al, 1995) and the multivariate regression model were utilized to examine the effect of board size and corporate ownership structure on earnings management. The results consistent with the earlier researches such as Al-Fayoumi et al (2010);Koh, (2003); Teshima & Shuto, (2008);and Yang et al, (2008) showed that the institutional ownership and the board size have a negative significant effect on the earnings management while the effect of the managerial ownership on the earnings www.ccsenet.org/ijbm…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The adjusted Jones Model (Dechow et al, 1995) and the multivariate regression model were utilized to examine the effect of board size and corporate ownership structure on earnings management. The results consistent with the earlier researches such as Al-Fayoumi et al (2010);Koh, (2003); Teshima & Shuto, (2008);and Yang et al, (2008) showed that the institutional ownership and the board size have a negative significant effect on the earnings management while the effect of the managerial ownership on the earnings www.ccsenet.org/ijbm…”
Section: Resultssupporting
confidence: 82%
“…The result documents that as managerial ownership rises, earnings management reduces not only large levels of managerial ownership but also low levels of managerial ownership. The study conducted by Yang, Lai and Tan (2008) on the firms quoted on the Taiwanese Stock Market for the period 1997-2004 suggest that the relation between earnings management and managerial ownership is a positively statistically significant. On the other hand, Gulzar and Wang (2011) find the relation between earnings management and managerial ownership is a negatively statistically significant on Chinese firms.…”
Section: Earnings Management and Managerial Ownershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the mixed results mentioned above and by Yang et al (2008) who find that discretionary accruals first increase and then decrease with executive ownership for firms listed in Taiwan, the second objective of our study is to examine the impact of managerial ownership on real earnings management. We do not, however, predict the sign of the relationship between managerial ownership and real earnings management for there is no consensus regarding the results of prior studies.…”
Section: Ownership Structure and Earnings Managementmentioning
confidence: 99%
“…Therefore, this study first seeks to include independent directors as one of the director characteristics to examine the monitoring role of the directors in deterring real earnings management. As to the ownership structure, based on prior research that provides mixed results regarding the impact of director ownership on discretionary accruals earnings management (Cornett, Marcus, & Tehranian, 2008;Dechow et al, 1996;Garcí a-Meca & Sá nchez-Ballesta, 2009;Sá enz Gonzá lez & Garcí a-Meca, 2007;Teshima & Shuto, 2008;Yang, Lai, & Tan, 2008), director ownership is the second factor that is included in the board member characteristics referred to in this study.…”
Section: Board Member Characteristics and Real Earnings Managementmentioning
confidence: 99%